Do you know this syndrome? Você conhece esta síndrome? - Laura Maria Andrade Silveira; Andréia Nogueira Ramos; Isadora Rosado do Amaral; Vitoria Regina Pedreira de Almeida Rêgo (Sociedade Brasileira de Dermatologia, 2013)
Congenital Hypertrichosis Lanugionsa is a rare autosomal dominant genetic disorder, with fewer than 50 cases reported in the literature. It is characterized by excessive lanugo hair, sparing only the mucous membranes, palms and soles. It may be associated with other organic abnormalities and should form part of the dermatologist's current knowledge. We discuss some aspects of the syndrome in question arising from the case report of a 2-year-old female patient, black, with classic clinical presentation, with no other associated congenital abnormalities. A hipertricose Lanugionsa Congênita é uma desordem genética rara, autossômica dominante, com menos de 50 casos descritos na literatura. É caracterizada por pêlo lanugo excessivo, poupando apenas membranas mucosas, palmas e plantas. Pode estar associada a outras anormalidades orgânicas, devendo ser de conhecimento do dermatologista. Discutiremos aspectos da síndrome em questão a partir do relato de caso de uma paciente do sexo feminino, negra, 02 anos, com apresentação clínica clássica, sem outras anormalidades congênitas associadas.